The Value of Contrast-Enhanced Ultrasound versus Doppler Ultrasound in Grading Renal Artery Stenosis - Cui, Yanhua (Biomed Res Int, 2020)
OBJECTIVE: This study is aimed at exploring the accuracy of contrast-enhanced ultrasound (CEUS) in grading renal artery stenosis. METHODS: 122 renal arteries with suspected renal artery stenosis were selected. DSA, DUS, and CEUS were performed for all patients with suspected renal artery stenosis in the research. DSA was selected as the gold standard. The sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of CEUS or Doppler ultrasound (DUS) in the diagnosis of renal artery stenosis were analyzed. The consistency between CEUS and digital subtraction angiography (DSA) was compared. The accuracy of DUS or CEUS in grading renal artery stenosis was assessed by the area under the receiver operating characteristic (ROC) curves and compared between groups. RESULTS: The sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of CEUS in the diagnosis of renal artery stenosis were 88.9%, 87.8%, 88.5%, 93.5%, and 80.0%, respectively. There was no significant difference in grading renal artery stenosis between CEUS and DSA (X(2) = 0.643, P = 0.424). 77 of the 122 renal arteries were diagnosed with the stenosis rate more than 30% by CEUS. Compared with the results of DSA, the kappa value of CEUS was 0.749 (P < 0.05). CONCLUSION: CEUS is accurate in grading renal artery stenosis, and it may represent the method of choice in diagnosing renal artery stenosis.